1993
DOI: 10.1111/j.1365-2796.1993.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome with insulin‐dependent diabetes mellitus: contiguous gene syndrome on chromosome 11p

Abstract: Long QT syndrome (Romano-Ward syndrome) and insulin-dependent diabetes mellitus (IDDM) have been documented as being linked with gene(s) on chromosome 11p although concurrence of the two disorders has not been reported. Our case is a 13-year-old boy with Romano-Ward syndrome accompanied by IDDM. The long QT syndrome seemed to be transmitted in an autosomal-dominant mode because the Q-T intervals of his father and paternal grandfather were longer than normal. There was no family member with an abnormally high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…SCN5A) related to cardiac ion channels have been linked to SID [32][33][34]. Furthermore, long QT syndrome (Romano-Ward syndrome) and type 1 diabetes have been linked with a gene(s) on chromosome 11p [43]. Moreover, a twin study showed that QTc is significantly longer in type 1 diabetes twins than in non-diabetic twins, further lending support to this possibility [44].…”
Section: Genetic Factorsmentioning
confidence: 89%
“…SCN5A) related to cardiac ion channels have been linked to SID [32][33][34]. Furthermore, long QT syndrome (Romano-Ward syndrome) and type 1 diabetes have been linked with a gene(s) on chromosome 11p [43]. Moreover, a twin study showed that QTc is significantly longer in type 1 diabetes twins than in non-diabetic twins, further lending support to this possibility [44].…”
Section: Genetic Factorsmentioning
confidence: 89%